Rhetorical structure and politeness strategies in complaint letters used by international students in a Thai ELF context - Nham, Ngoc Thi; Xirui Cai,; Anchalee Wannaruk, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Making a complaint in any language is not an easy task. The complainer might run the risk of impairing the relationship between him/her and the hearer. In Thailand, international students use English as a medium of communication among one another and with local people. This English as a lingua franca (ELF) context was considered appropriate to investigate the rhetorical structure and politeness strategies used in complaint letters written by the international students in order to see their use of polite strategies and the factors influencing their choices. Forty graduate international students were asked to write two complaint letters to local addressees in the university contexts, one to a person of a higher status and the other to a person of equal status. Some of them were also interviewed. Based on Hartford & Mahboob’s framework (2004), seventeen moves were found in the rhetorical structure of the complaint letters. As to politeness strategies, more negative strategies were used in the moves of Complaint and Request while more positive strategies were found to set a common ground in Introduction, Attention getter, and Background. The factors influencing the choice of politeness strategies included social status, social distance, pragmatic transfer, and L2 input. The interviews reveal different views between the complainers and the complainees on the effectiveness of politeness strategies adopted.